PECULIARITIES OF REGULATING CONSTRUCTION BUSINESS IN GEORGIA - Vasil Kikutadze; David Sikharulidze; Maka Piranashvili (European Scientific Journal, ESJ, 2014)
Since 2004 Georgia has been carrying out radical reforms to regulate the construction sector. After the cancellation of the Ministry of Architechture and Construction of Georgia the regulation of the field was delegated to the Spacial Planning and Construction Policy Department at the Ministry of Economy and Sustainable Development of Georgia. In the process of regualting construction business, one of the most significant places is attributed to the construction quality control which means either the state or the private customer should set strict supervision on the architectural-building business considering the essence and specificities of the construction production. Developed countries have obtained and possess the complex system of quality assurance and control in the sphere of construction along others. It covers three stages: supervision of the state, of local authority and of insurance companies.